Der König und sein Beichtvater Friedrich Wilhelm IV. und Carl Wilhelm Saegert. Briefwechsel 1848 bis 1856. Red.: Mathias Friedel - Baumgart, Winfried (Deutsche Geschichtsquellen des 19. und 20. Jahrhunderts (DGQ), 2016)
In the turmoil of the revolution of 1848 the vacillating Prussian king Frederick William IV found support in Carl Wilhelm Saegert, director of a school for the deaf and dumb in Berlin. This individual gave the king advice in all matters of domestic and foreign policy. Not being a member of the aristocracy Saegert could not gain access to a governmental post and therefore had do play his role through the back door. - In addition to their secret correspondence Saegert's diary for the revolutionary months of 1848 is published in extenso.